Evaluation of Reduction in the Performance of a Small UAV After an Aileron Failure for an Adaptive Guidance System - Ducard, G.; Kulling, K.C.; Geering, H.P. (2007 American Control Conference, 2007)
After an actuator failure, the performance of an aircraft is degraded. If a fault detection and isolation system is available in the flight control system, the knowledge of the failure can be used to evaluate the new aircraft performance. Based thereon, a supervision system decides whether the mission can still be continued or if it should be aborted and have the aircraft redirected to the base station. In both cases, the aircraft should still be guided along a trajectory that is compatible with the new flying properties of the airplane. This paper focuses on an aileron failure and shows how the degraded flying performance can be evaluated and used to reconfigure the guidance system. Simulation results show that if the reduced performance due to the actuator failure is taken into account, the safety of the mission is improved.